Husband Support For The Implementation Of Antenatal Care In Primigravid Pregnant Women In Bpm Ny”N” Tambak Rejo Village, Waru District, Sidoarjo District Year 2020 - Siti Rofiatun; Atik Setiawan Wahyuningsih (Journal for Research in Public Health, 2023)
The health of pregnant women is one of the important aspects to consider in a woman's life cycle because during her pregnancy unexpected complications can occur. Every pregnant woman will face risks that can threaten her life. Therefore, every pregnant woman needs care during her pregnancy (Salmah, 2016). The purpose of this study was to determine the influence of husband's support on the implementation of Antenatal Care in primigravida pregnant women at BPM NY "N" Waru Sidoarjo in 2020.The design of this study was cross sectional analytic. The population is all primigravida pregnant women at BPM Ny "N" Waru Sidoarjo 2020. The sample is partly primigravida pregnant women at BPM Ny "N" Waru Sidoarjo 2020 totaling 32 respondents. The sampling technique in this research is non probability sampling, namely purposive sampling type sampling technique. In collecting data from respondents, the next step the researcher took was processing the data by editing, coding, scoring, tabulating, data entry, and cleaning. Data analysis in this study used the Chi Square test. From the results of the Chi Square test, if the p value <level of significant (0.05), the conclusion is that Ho is rejected and H1 is accepted, meaning that there is a relationship between husband's support for the implementation of Antenatal Care in primigravid pregnant women in BPM NY "N" Waru Sidoarjo in 2020. The husband's lack of support is due to the husband's lack of knowledge about the importance of ANC and the husband's work. To overcome this problem, counseling can be carried out to mothers and families about the importance of ANC visits for early detection of pregnancy and prevention of early pregnancy complications so that mothers and children are healthy.